Breaking Barriers: Using Open Data to Strengthen Pathways in Community-Campus Engagement for Community Action on Environmental Sustainability - Leigha McCarroll; Eileen O’Connor; Jason Garlough (Engaged Scholar Journal, 2019)
The goal of this field report is to share learnings on productive dialogue between, and among, communities and campuses. Specifically, we will reflect on practical applications of co-creating a brokering tool to strengthen connections between local environmental non-profit organizations and the six postsecondary institutions in the National Capital Region (Ottawa/Gatineau). The report outlines a process of standardizing and visually depicting data on university and college engagement opportunities, created with an aim of making it easier for potential community partners, students, faculty, and even the general public to search, filter, and discover new programs, researchers, and services that match their interests.